2009
DOI: 10.1007/s10531-009-9694-3
|View full text |Cite
|
Sign up to set email alerts
|

Tree size and herbivory determine below-canopy grass quality and species composition in savannahs

Abstract: Large single-standing trees are rapidly declining in savannahs, ecosystems supporting a high diversity of large herbivorous mammals. Savannah trees are important as they support both a unique flora and fauna. The herbaceous layer in particular responds to the structural and functional properties of a tree. As shrubland expands stem thickening occurs and large trees are replaced by smaller trees. Here we examine whether small trees are as effective in providing advantages for grasses growing beneath their crown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 41 publications
(61 reference statements)
6
40
1
1
Order By: Relevance
“…Higher nitrogen and phosphorus contents in grasses growing beneath trees compared to grasses growing outside of tree canopies were found in both dry and wet season in KNP (Treydte et al 2008). Further, several studies reported that particularly P. maximum, a preferred forage grass species, grew significantly more often beneath tree canopies (East and Felker 1993;Treydte et al 2009a), which could also be confirmed by our study. Moreover, Ben-Shahar and Coe (1992) found that zebra and blue wildebeest move to patches where the grass community contains a high proportion of nutritional species such as P. maximum.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Higher nitrogen and phosphorus contents in grasses growing beneath trees compared to grasses growing outside of tree canopies were found in both dry and wet season in KNP (Treydte et al 2008). Further, several studies reported that particularly P. maximum, a preferred forage grass species, grew significantly more often beneath tree canopies (East and Felker 1993;Treydte et al 2009a), which could also be confirmed by our study. Moreover, Ben-Shahar and Coe (1992) found that zebra and blue wildebeest move to patches where the grass community contains a high proportion of nutritional species such as P. maximum.…”
Section: Discussionsupporting
confidence: 89%
“…Owen-Smith (2002) likewise termed high nutrient quality patches as "limited intake resource", providing highly nutritious food but only in limited abundance. A previous study in KNP indicated that grass leaf nitrogen contents were up to 40% higher beneath large trees compared to the same grass species growing outside of tree canopies (Treydte et al 2009a). Higher nitrogen and phosphorus contents in grasses growing beneath trees compared to grasses growing outside of tree canopies were found in both dry and wet season in KNP (Treydte et al 2008).…”
Section: Discussionmentioning
confidence: 82%
“…In general, the presence of tall trees enhanced grass N and P contents at all study sites inside KNP, which confirmed the findings of (Treydte et al, 2009). In contrast to wildlife sites, no influence of trees on grass leaf nutrient content was found for livestock sites.…”
Section: (H4) Higher Grass Nutrients When Browsers Are Presentsupporting
confidence: 85%
“…The persistence of large single standing trees in the communal areas is highly beneficial to biodiversity and savanna function (Belsky et al, 1993;Manning et al, 2006;Treydte et al, 2009). The local abundance of rare tree species is a concern in communal areas (Shackleton et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…These classes relate to the influence of fire and herbivory, their function in the landscape, as well as human utilization (Belsky et al, 1993;Scholes and Walker, 1993;Bond and Midgley, 2000;Shackleton and Shackleton, 2004;Neke et al, 2006;Treydte et al, 2009).…”
Section: Comparison Of Woody Vegetation Cover and Height Distributionsmentioning
confidence: 99%